Factors Influencing the Success of Inclusive Education for Children with Dyslexia - PURBA, FITRI VERONICA; SILALAHI, ROSIANI; LOMBU, ARYANTO; SIMORANGKIR, MELDA RUMIA ROSEMARY (PERFECT EDUCATION FAIRY, 2025)
This study explores factors influencing the success of inclusive education for children with dyslexia. A descriptive qualitative approach using literature review was employed to analyze relevant studies. The findings reveal that the success of inclusive education is influenced by internal factors such as the severity of dyslexia and emotional regulation; the role of teachers, including empathy and competence in multisensory methods; curriculum and teaching methods utilizing technology or multisensory approaches; and supportive school environments. This research highlights the importance of collaboration among teachers, families, and communities in creating an inclusive and effective learning environment.